2011
DOI: 10.1159/000314617
|View full text |Cite
|
Sign up to set email alerts
|

Fetoscopic Endotracheal Occlusion for Severe Isolated Diaphragmatic Hernia: Initial Experience from a Single Clinic in Brazil

Abstract: Objective: To report on the initial experience in a single Brazilian university clinic of the use of fetoscopic endotracheal occlusion (FETO) to treat severe isolated congenital diaphragmatic hernia (CDH). Methods: The inclusion criteria for FETO for this prospective study were isolated CDH and intrathoracic herniation of the liver, as well as the lung area to head circumference ratio (LHR) <1.0. The main variables evaluated were LHR and observed to expected (o/e) LHR before and after FETO, gestational age (GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 30 publications
8
34
1
2
Order By: Relevance
“…In this issue of Fetal Diagnosis and Therapy , two larger case series from Brazil are also published. The reported outcomes of the study by Ruano et al [16] and Peralta et al [117] are quasi duplicates of what we reported ( table 1 ). …”
Section: Current Percutaneous Feto Techniquesupporting
confidence: 79%
See 1 more Smart Citation
“…In this issue of Fetal Diagnosis and Therapy , two larger case series from Brazil are also published. The reported outcomes of the study by Ruano et al [16] and Peralta et al [117] are quasi duplicates of what we reported ( table 1 ). …”
Section: Current Percutaneous Feto Techniquesupporting
confidence: 79%
“…In recent years, it has become apparent that fetal intervention can be offered through minimally invasive access and is safe for the mother. Fetal Diagnosis and Therapy now publishes 2 additional clinical series with percutaneous fetoscopic endoluminal tracheal occlusion (FETO), suggesting an increased survival rate after fetal surgery [14][15][16][17] . Though the published experience seems to demonstrate variable degrees of benefit of fetal therapy, one should remember this remains an experimental procedure, in the sense that it is not a therapy with proven efficacy (as is the case for many other fetal therapies).…”
Section: A Special Issue On Cdhmentioning
confidence: 99%
“…A similar increase in survival after TO (although slight differences in protocols) has been observed in Brazil and Germany [36][37][38]. Obviously, this claim of improved outcome must now be proven in appropriately designed trials.…”
Section: Trials On Feto Vs Expectant Managementsupporting
confidence: 58%
“…The FETO procedure has been described in detail 22,23,28 . Briefly it consists of the percutaneous fetoscopic insertion of a balloon into the fetal trachea, which in general is performed at approximately 26-28 (range, [23][24][25][26][27][28][29][30][31][32][33] weeks' gestation. The balloon is preferentially removed in utero at approximately 34 weeks by tracheoscopy or ultrasound-guided puncture.…”
Section: Methodsmentioning
confidence: 99%